Research on the Practice of Data Assets Entering into the Table of Haitian Ruisheng Company - Gao, Yanfang; Mo, Bixia (Asia Pacific Economic and Management Review, 2025)
This study takes Haitian Ruisheng as a typical case to explore the impact of data assets listing on enterprises and practical experience. After the implementation of the Interim Provisions on Accounting Treatment of Enterprise Data Resources in 2024, as one of the few listed companies that included data resources into “inventory”, Haitian Ruisheng realized the explicit value of data assets through accurate division of data resource types, refined cost accounting and comprehensive information disclosure. The study found that the listing of data assets significantly improved the profitability of enterprises. In 2024, the net profit increased by 105.24% year on year, and the return on equity turned from negative to positive. The market valuation increased significantly, and the price-to-sales ratio, price-to-book ratio and price-to-earnings ratio were significantly higher than the industry average, reflecting the high recognition of enterprise value in the market. At the same time, the listing measures stimulated the innovation momentum of enterprises, promoted the large-scale production of data assets and business model innovation, and the operating revenue in 2024 increased by 39.45% year on year. Haitian Ruisheng practice shows that the correct classification data resources scientific calculation value and full disclosure of information is the core of assets into the table data path, for enterprise provides reproducible operation pattern, also to improve data assets accounting rules, the deepening marketization of data elements configuration provides an important reference.